An Observational Study into the Levels of Evidence Presented at the Combined Services Orthopaedic Society Annual Meeting. Issue 3 (1st September 2011) - Bonner, Tim; Mountain, A; Eardley, WGP; Clasper, JC
Abstract : Objectives: The role of Evidence Based Medicine in clinical care is to provide a framework for the integration of expertise, current evidence and the needs of the individual patient. Research presented at scientific meetings is an important source of such evidence, informing clinical decision making both on military operations and in home nation health care systems. The aim of this study is to review the levels of evidence presented at the Combined Services Orthopaedic Society (CSOS) and two other related scientific meetings. Methods: Retrospective review of abstracts presented at the annual scientific meetings of the CSOS, Society of Military Orthopaedic Surgeons (SOMOS) and the British Trauma Society (BTS). Basic science studies, animal studies, cadaveric studies, surveys and guest lectures were excluded. Research abstracts were categorised according to the Centre for Evidence- Based Medicine's (CEBM) hierarchy of evidence. Statistical comparison was performed to investigate differences in evidence levels presented at each scientific meeting and between each year of the CSOS meeting. Results: 596 abstracts met the inclusion criteria for this study (179 CSOS, 173 SOMOS, 244 BTS). Level IV evidence accounted for the majority of presented abstracts at each meeting (72.6% CSOS, 69.4% SOMOS, 68.9% BTS). Level I evidence was uncommon at each meeting (6.1% CSOS, 5.2% SOMOS, 2.9% BTS). There was no statistical difference in the evidence levels presented at the three scientific meetings. Conclusions: The proportion of comparative clinical studies (Levels I-III) presented at military or trauma societies' scientific meetings reflects the difficulty of performing research in emergency surgery. This is further exacerbated in the military environment where operational commitments and delivery of care take priority. However, the future value of comparative clinical research in battlefield healthcare could have an enduring legacy that shapes trauma care for many decades.